Harmonic excitation response of standard ultrasonic horn designs for machining nomex honeycomb core composite - Khurram Hameed Mughal; Muhammad Asif Mahmood Qureshi; Nasir Hayat; Zia ul Rehman Tahir; Shahzad Ahmad; Adnan Maqbool; Syed Farhan Raza; Asif Ali Qaiser; Fazal Ahmad Khalid; Zhang, Jianfu (Penerbit Universiti Kebangsaan Malaysia, 2024)
Ultrasonic horn plays a vital role in achieving vibration amplitude at tool end (VATE) by enhancing output displacement of piezoelectric ultrasonic transducer suitable for efficient machining of advanced composites. Higher vibration amplitude enhances ultrasonic machining quality, surface integrity and dimensional accuracy of Nomex honeycomb composite (NHC) while reducing cutting forces. Furthermore, low stress concentrations allow ultrasonic tool to have more safety factor and longevity. Ultrasonic horn is designed to enhance displacement amplitude of piezoelectric ultrasonic transducer and get optimum VATE while keeping stresses in acceptable limits to avoid failure at very high operating frequency of ultrasonic machining system. In this research, variety of standard ultrasonic horns (SUH) were designed with same length and end diameters; and were tested under similar operating conditions, using finite element method. The ultrasonic actuation of the horn exploits the first axial mode of horn vibration. Harmonic response analysis was carried out to determine axial modal frequencies (AMF), VATE, stresses, and factor of safety for performance evaluation. VATE attained by step horn was found to be greatest among all other SUHs for frequency ratio greater than one, but may be prone to early failure due to high stress concentrations. VATE achieved by third order Bezier, Gaussian, exponential, catenoidal, conical and second order Bezier horns were found less than that of step horn by 11.7 %, 16.6 %, 16.7 %, 17 %, 16.73 % and 18 % respectively. However, 44.2 %, 43.43 %, 42.5 %, 43.5 %, 42.8 % and 37.67 % reduction of stresses was achieved by Gaussian, exponential, catenoidal, conical, second and third order Bezier horns respectively. Outcomes of present work would be beneficial for designers, researchers, scientists, and manufacturers of ultrasonic machine tool to select appropriate SUH designs according to requirements.